2015
DOI: 10.1016/j.cbpa.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Proteome sequencing goes deep

Abstract: Advances in mass spectrometry have transformed the scope and impact of protein characterization efforts. Identifying hundreds of proteins from rather simple biological matrices, such as yeast, was a daunting task just a few decades ago. Now, expression of more than half of the estimated ~20,000 human protein coding genes can be confirmed in record time and from minute sample quantities. Access to proteomic information at such unprecedented depths has been fueled by strides in every stage of the shotgun proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 58 publications
0
92
0
1
Order By: Relevance
“…A crosslink contact also contains (relatively low resolution) spatial information in itself. Recent technological advances [53,54] have now rendered this method applicable to physiologically important biological assemblies that are difficult to examine using more traditional structural techniques. This technology is therefore optimally suited for studying the architecture of large protein complexes and their interaction partners in their native environment and on a medium to large scale.…”
Section: Recent Advances In Xl-ms Methodsologymentioning
confidence: 99%
“…A crosslink contact also contains (relatively low resolution) spatial information in itself. Recent technological advances [53,54] have now rendered this method applicable to physiologically important biological assemblies that are difficult to examine using more traditional structural techniques. This technology is therefore optimally suited for studying the architecture of large protein complexes and their interaction partners in their native environment and on a medium to large scale.…”
Section: Recent Advances In Xl-ms Methodsologymentioning
confidence: 99%
“…Comprehensive studies on the proteomes of cells, tissues, or organisms have been reported (e.g. Addona et al , 2009; Nilsson et al , 2010; Beck et al , 2011; Nagaraj et al , 2011; for review, see Bensimon et al , 2012; Kulak et al , 2014; Wilhelm et al , 2014; Hein et al , 2015; Richards et al , 2015), but accurate quantitative information on proteins expressed at low levels remains scarce. As a consequence, published estimates for the abundance of specific proteins sometimes vary over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these have been aided by developments in mass spectrometry (MS)-based analysis, enabling higher sensitivity and a higher dynamic range of quantification. (23)(24)(25)(26) In addition, over the past decade, biochemical and cell biological fractionation, such as chromatography or centrifugationbased separations, have increased in efficiency and resolution. Thus, multiple separations can now more easily be combined for sequential multidimensional proteome analysis ( Figure 3).…”
Section: Building the Foundation For Genomic In Personalized Medicinementioning
confidence: 99%